Evaluation of Total Female and Male Aedes aegypti Proteomes Reveals Significant Predictive Protein–Protein Interactions, Functional Ontologies, and Differentially Abundant Proteins - Abubakar Shettima; Shaleni Joseph; Intan H. Ishak; Syahirah Hanisah Abdul Raiz; Hadura Abu Hasan; Nurulhasanah Othman (Insects, 2021)
Aedes aegypti is a significant vector for many tropical and subtropical flavivirus diseases. Only the female mosquito transmits pathogens, while the male plays a vital role in mating and species continuity. This study explored the total proteomes of females and males based on the physiological and genetic differences of female and male mosquitoes. Protein extracts from mosquitoes were analysed using LC–ESI–MS/MS for protein identification, protein interaction network analysis, functional ontology enrichment, and differential protein abundance analyses. Protein identification revealed 422 and 682 proteins exclusive to males and females, respectively, with 608 common proteins found in both sexes. The most significant PPIs (<1.0 × 10−16) were for common proteins, followed by proteins exclusive to females (<1.0 × 10−16) and males (1.58 × 10−12). Significant functional enrichments were observed in the biological process, molecular function, and cellular component for the male and female proteins. The abundance of the proteins differed, with one protein showing an increase (elongation factor 1 α, EF1α) and two showing reductions (actin family) in females versus males. Overall, the study verified the total proteomes differences between male and female Ae. aegypti based on protein identification and interactions, functional ontologies, and differentially abundant proteins. Some of the identified proteins merit further investigation to elucidate their roles in blocking viral transmission.